Validity and Reliability Analysis of Reading Comprehension Skill Test Using Islamic English Texts - Putria, Asa Bani (Universitas Negeri Semarang, 2023)
One of the requirements for graduation in Islamic universities is the ability to master English. Students encounter obstacles in fulfilling these requirements, especially non-English study program students. This study aims to prove the validity and estimate the reliability of the reading comprehension skills test instrument using Islamic English texts. The method used in this study was the research and development method proposed by Mardapi. Proof of content validity used the Aiken's V formula while estimation of reliability between raters used a two-way ANOVA test which was then calculated using Hoyt's formula. The research data shows that the Aiken V coefficient value for each statement item is more than 0,3. It can be said that all aspects are valid. The estimated reliability of the two-way ANOVA test yields a value of 0,94. It can be said that this instrument is quite reliable. Thus, it can be concluded that the test instrument for reading comprehension skills of Islamic English texts has high validity and reliability among raters is quite strong and is expected to be used as a reference for the test instrument makers.